The study of sustainable development of the regions: tendencies, results and gaps - Olga Tuzhikova (Transactions of the Karelian Research Centre of the Russian Academy of Sciences, 2015)
The article discusses the recent achievements in the field of regional sustainable development study and the dynamics of scientific interest in this phenomenon. The approaches and tendencies in studying the concept of sustainable development in general are analyzed. The main directions of scientific thought concerning sustainable development of the regions are defined. Perspective yet underestimated aspects of regional sustainable development are described. The key directions for the further study in this field are outlined.